Kurikulum dan metode pembelajaran antar negara: Penelitian - Inggi Turnando; Thamrin, Ahmat Fauzan; Sari, Mini Puspita (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to conduct a comparative analysis of curricula and teaching methods across countries to identify patterns, strengths, and challenges within contemporary global education systems. Employing a qualitative approach through a literature-based study, this research examines scholarly articles, international reports, and educational policy documents from several countries, including Finland, Singapore, Japan, the United States, and Indonesia. Content analysis and thematic analysis were used to investigate curriculum orientation, implementation flexibility, pedagogical approaches, and their impact on twenty-first-century competencies. The findings reveal that high-performing countries commonly adopt competency-based curricula supported by student-centered learning, strong teacher professionalism, and robust technological integration. Finland excels in curriculum flexibility and student well-being; Singapore demonstrates strength through rigorous academic standards and structured learning; while Japan effectively integrates cultural values with pedagogical precision through lesson study. Indonesia shows positive progress with the Merdeka Curriculum, yet its implementation remains challenged by teacher readiness, digital infrastructure, and disparities in educational quality.